6-Thioguanine nucleotide accumulation in erythrocytes during azathioprine treatment for systemic connective tissue diseases: a possible index for monitoring treatment. Issue 2 (February 1993) - Schmiegelow, K; Kriegbaum, N J
Abstract : BACKGROUND: Owing to adverse pharmacokinetics, azathioprine treatment may fail to induce a satisfactory clinical response in systemic connective tissue diseases. The major intracellular cytotoxic metabolites of azathioprine are 6-thioguanine nucleotides (6TGNs). METHODS: To assess whether the erythrocyte accumulation of 6TGN is a clinically applicable index for monitoring azathioprine treatment, erythrocyte accumulation of 6TGN was measured in patients with rheumatoid arthritis (n = 12), systemic lupus erythematosus (n = 7), polyarteritis nodosa (n = 2), myositis (n = 1), or leukocytoclastic vasculitis (n = 1). Ages ranged from 28 to 75 (median 58) years. RESULTS: Erythrocyte accumulation of 6TGN varied among the patients from 20 to 303 (median value 95) nmol/mmol haemoglobin. No significant correlation was found between erythrocyte accumulation of 6TGN and the dose of azathioprine/kg body weight, the age of the patients, the duration of treatment, or the presence of myelotoxicity or hepatotoxicity. The interindividual coefficient of variation (CV) in the erythrocyte accumulation of 6TGN/mg azathioprine/kg body weight was 0.65. The median intraindividual CV in erythrocyte accumulation of 6TGN at an unchanged dose of azathioprine was 0.09 (19 patients; range 0.03-0.27). CONCLUSIONS: The low intraindividual variation compared with the high interpatient variation in erythrocyte accumulation of 6TGN implies that erythrocyte accumulation of 6TGN may be clinically applicable for monitoring azathioprine treatment. Prospective studies are needed to clarify the relation between the erythrocyte accumulation of 6TGN and the clinical response to treatment, and to establish recommendations for dose modifications.